Evaluating the effectiveness of System Engineering on Organization Management Using Structural Equations Modeling - Shabaninejad, Behzad; Esmaielian, Gholamreza; Fekri, Roksana (Ciência e Natura, 2015)
System Engineering, as a new implication and major, plays an outstanding role in the organizations. This system pays attention to the project beneficiaries, product designing, data architecture, customers’ satisfaction, organizational integration, and applying organizational knowledge that has increased efficiency and productivity in an organization. Evaluating the effectiveness of system engineering on the organizational management targets (including product innovation, strategic planning) is considered to be one of the main issues engaged with the organizations. The purpose of this study is to evaluate the relation between system engineering, strategic planning, and product innovation engineering and to provide a comprehensive model for the execution of system engineering. For these purposes, specific processes have been identified for system engineering, strategic planning, and product innovation engineering. A questionnaire was prepared and distributed among the personnel at Iran Aircraft Manufacturing Co. Three assumptions were discussed (the influence of system engineering on strategic planning, the influence of system engineering on product innovation engineering, and the influence of strategic planning on product innovation engineering) and were evaluated by using of structural equations modeling (LISREL Software). The aforesaid influence was confirmed respectively with factor load of 5/10 and 2/84 and 3/66.